Implementasi Implementation Of Health Care Tasks Throughfamily Counseling For Tuberculosis Patients At The Sikumana Community Health Center - Lidia Agustina Tokan; Maria Agustina Making; Pius Selasa; Oklan Liunokas; Ridhoyanti Hidayah; Febtian Cendradevi Nugroho; Yulianti Kristianti Banhae; Emilia Erningwati Akoit (Poltekkes Kemenkes Kupang, 2025)
Tuberculosis (TB) is an infectious disease with a high number of cases in Indonesia, including in the working area of the Sikumana Community Health Center. Low patient compliance in undergoing therapy is one of the main challenges. Families play an important role in accompanying patients, from monitoring medication intake and providing nutrition to giving emotional support. To determine the effect of implementing health care tasks through family support on tuberculosis patients at the Sikumana Community Health Center. Quantitative research with a pre-experimental one-group pretest-posttest design. The research sample consisted of 30 respondents who were family members of tuberculosis patients. The instruments used were a family support questionnaire covering five family health tasks and a SAP on Family Support. Data analysis was performed using the Wilcoxon test. Results: In the pretest, most families were in the adequate (53%) and poor (46.7%) categories, with none in the good or very good categories. After the intervention, the posttest results showed a significant improvement, with 60% of respondents in the good category and 20% in the very good category. The Wilcoxon test produced a p-value < 0.001, indicating a significant effect of family support on the improvement of health care tasks. Family support was proven to increase family involvement and understanding in supporting TB patient treatment. Suggestions: Family support needs to be made a sustainable strategy in primary care, with a broader sample coverage and innovative interactive educational media to increase effectiveness.